From archives to the digital ecosystem: heritage and scientific communication surrounding Fray Mamerto Esquiú - Clissa, Karina (Scripta Mundi, 2026)
This article analyzes the transformation of the Franciscan archive of Fray Mamerto Esquiú into a digital environment as a strategy to articulate historical research, scholarly communication, and public history. Based on an interdisciplinary university project, it examines how the digitization, transcription, and critical contextualization of the collection make it possible to broaden audiences, strengthen community participation, and situate religious heritage within contemporary debates on memory and citizenship. The study draws on a systematic review of the bibliographic production on Esquiú, encompassing more than one hundred and fifty years of biographical, devotional, political-religious, and institutional publications. This methodological approach made it possible to identify dominant interpretive trends, as well as persistent gaps regarding his public activity, his correspondence, and his reflections on civic virtue. The results show that the historiographical reception of Esquiú has been marked by cycles of intermittent attention and by the predominance of edifying approaches, which has limited his projection toward broader forms of scientific communication. In this context, the digital archive emerges as a key tool for reorganizing the field, fostering new readings, and promoting mediations oriented toward diverse audiences. It is concluded that the integration of digital archives, public history, and heritage contributes to strengthening cultural sustainability, in line with the objectives of SDG 11, and makes it possible to transform a convent-origin collection into a shared cultural asset with social projection.
Keywords: scientific communication; Public history; digital archive; cultural sustainability